“Euro-Mineral” and “Euro-Gem” 2010 in Sainte Marie aux Mines, Alsace, France – perfectly prepared geotouristic product for everyone - Łodziński, Marek (Geotourism/Geoturystyka, 2025)
The paper is a brief information about largest in Europe exhibition and fair of minerals and precious stones (“Exposition-Bourse Internationale de Mineraux-Fossiles-Pierres Precieuses-Bijoux”), which is held each year, in mid June, in a small town Sainte Marie aux Mines in Alsace, France. The town, located on the eastern slopes of the Vosges Mts., is a historical mining camp of silver ores. The exhibition, better known under the working names “Euro-Mineral” and “Euro-Gem”, still continues the traditional links with attracts not only minerals and fossils collectioners, prospectors and dealers but also jewellers, scientists, travellers and common tourists from all over the world – all those, who are interested in minerals and rocks from the Earth and from the Space.